2018
DOI: 10.1111/aab.12469
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of application nursery cultivation arbuscular mycorrhizal seedling in watermelon in the field

Abstract: Arbuscular mycorrhizal fungi (AMF) colonisation of plant root facilitates the absorption of nutrients such as phosphorus (P) and enhances plant biotic and abiotic resistance generally. However, arbuscular mycorrhiza (AM) colonisation decreases with application of chemical fertiliser. Here, we investigated whether AMF inoculation in nurseries would facilitate AM colonisation and take physiological and ecological functions in watermelon (Citrullus lanatus) in the field. Pot experiments were carried out to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…Inoculating plants with AMF increased significantly the concentrations of NPK nutrients within plant shoots. This might be attributed to the concurrent increases that occurred in the absorbing area of the plant roots via the extended mycorrhizal hyphae (Wiedenhoeft, 2006); beside of the increases that took place in P availability in soil (Bi et al, 2018;Ren et al, 2019). Also, AMF inoculation probably utilized organic nitrogen (Chen et al, 2018;Bukovská et al, 2018;Hestrin et al, 2019) that was found in farm yard manure while decreased N loses from soil (Teutscherova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inoculating plants with AMF increased significantly the concentrations of NPK nutrients within plant shoots. This might be attributed to the concurrent increases that occurred in the absorbing area of the plant roots via the extended mycorrhizal hyphae (Wiedenhoeft, 2006); beside of the increases that took place in P availability in soil (Bi et al, 2018;Ren et al, 2019). Also, AMF inoculation probably utilized organic nitrogen (Chen et al, 2018;Bukovská et al, 2018;Hestrin et al, 2019) that was found in farm yard manure while decreased N loses from soil (Teutscherova et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During early growth, this direct contact between roots and PBMs can benefit plant growth, health and vegetable nutrient quality. 151,152 Some recent researchers have focused on applying AMF in vegetables to improve seedling characteristics, such as dry matter content and root system in watermelon, 153 onion 154 and tomato. 155 Also, rhizobacteria have shown some positive effects in increasing the resistance to salt stress on tomato, 154 aubergine, 155 lettuce 156 and zucchini seedlings.…”
Section: Microbial and Non-microbial Plant Biostimulantsmentioning
confidence: 99%
“…The reaction was then stopped by the addition of 2 ml of a mixture of ammonium molybdate, ammonium metavanadate and nitric acid (1:1:2, v:v:v). The liberated inorganic orthophosphate (P i ) was measured by spectrophotometric method (Ren et al, 2019;Zhang et al, 2021). Phytase activity was calculated as the difference between the P i concentration in the reaction solution with and without plant roots and expressed in milligrams of P i released per hour per gram of fresh weight.…”
Section: Phytase Activitymentioning
confidence: 99%